Visconti and the German dream : Romanticism, Wagner and the Nazi catastrophe in film - Huckvale, David (McFarland & Co., Inc., Publishers, 2012)
"This book explores the complex relationship between themes and ideals of German Romanticism; their impact on the Third Reich catastrophe; how the German Romantic movement led to Nazism, and contrasts the ways in which filmmakers have presented this continuum. Works discussed are Richard Wagner, Thomas Mann, Friedrich Nietzsche, Hans-Jürgen Syberberg, Ken Russell, Tony Palmer and others"--Provided by publisher.